2008
DOI: 10.1021/es702295f
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Polybrominated Diphenyl Ethers and Thyroid-Stimulating Hormone Associated with Lymphocytic Micronuclei in Chinese Workers from an E-Waste Dismantling Site

Abstract: In this study, we recruited 49 subjects from one village close to an electronic waste (e-waste) site (exposed group) and another located 50 km away from the e-waste site (control group). We found that serum levels of polybrominated diphenyl ethers (median PBDEs, 382 ng/g lipid weight; range, 77-8452 ng/g lipid weight) and thyroid-stimulating hormone (median TSH, 1.79 microIU/mL; range, 0.38-9.03 microIU/mL) and frequencies of micro-nucleated binucleated cells (MNed BNC; median, 5% per hundred; range, 0-96% per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(88 citation statements)
references
References 49 publications
1
85
2
Order By: Relevance
“…Since the release of ENGO reports, work has begun to emerge within the environmental toxicology literature that confirms those reports about the toxic hazards associated with e-waste processing (e.g., Osibanjo and Nnorom 2008;Williams et al 2008;Yuan et al 2008). For example, under laboratory conditions using aquatic toxicity testing methods, Dagan et al (2007) found a range of common household electronics such as PC components and cell phones to be highly toxic in terms of bioavailability of leached heavy metals.…”
Section: E-waste Researchmentioning
confidence: 89%
“…Since the release of ENGO reports, work has begun to emerge within the environmental toxicology literature that confirms those reports about the toxic hazards associated with e-waste processing (e.g., Osibanjo and Nnorom 2008;Williams et al 2008;Yuan et al 2008). For example, under laboratory conditions using aquatic toxicity testing methods, Dagan et al (2007) found a range of common household electronics such as PC components and cell phones to be highly toxic in terms of bioavailability of leached heavy metals.…”
Section: E-waste Researchmentioning
confidence: 89%
“…Abundant toxins, such as trace metals, polybrominated diphenyl ethers (PBDEs), and PCBs have been released into the environment due to use of primitive e-waste recycling processes [1][2][3][4][5][6][7][8]. High levels of persistent organic pollutants (POPs) and trace metals have been detected in the air, dust, soil, sediment, and biota samples around e-waste recycling sites, which may pose a threat to local residents and the ecosystem [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Unregulated e-waste recycling has resulted in the release of large quantities of PBDEs and other toxic chemicals into the environment, particularly in locations such as Qingyuan and Guiyu of South China Luo et al, 2011). So far, most of the previous research on chemicals released from e-waste has focused on measuring the concentration in topsoil, sediment, air (Ma et al, 2009;Wang et al, 2011a), as well as quantifying human exposure (Bi et al, 2007;Yuan et al, 2008). However, there is little information available on the potential for PBDEs to migrate within and be transported from e-waste contaminated soils.…”
Section: Introductionmentioning
confidence: 99%